Case Report: Surgical management of giant multiple aneurysms after Kawasaki disease in a teenager - Fischetti, Giuseppe; Giovannico, Lorenzo; Meliota, Giovanni; Di Bari, Nicola; Parigino, Domenico; Massari, Elena; Lombardi, Maristella; Vairo, Ugo; Bottio, Tomaso; Padalino, Massimo A. (Frontiers in Pediatrics, 2025)
Kawasaki disease (KD), or mucocutaneous lymph node syndrome, is a rare systemic inflammatory condition predominantly affecting children under 5 years of age. Complications such as giant coronary artery aneurysms, although rare due to advancements in treatment, remain life-threatening. Coronary artery bypass grafting (CABG) has been a well-established treatment for severe coronary lesions caused by KD. In rare cases of ischemic cardiomyopathy in pediatric patients, heart transplantation may be the only option. We report a case of a 15-year-old male with a history of KD diagnosed at 9 months of age, complicated by giant coronary aneurysms of the left anterior descending and right coronary arteries, who underwent a successful double CABG using the left internal mammary artery) and a saphenous vein graft.